Reducing implicit biases in classroom discussions. Issue 2 (3rd April 2022) - Mandhana, Dron M.; Caruso, Victoria
Abstract : Courses: Public Speaking, Survey of Communication Studies, Interpersonal Communication, Intercultural Communication. Objectives: This activity focuses on helping students (1) become aware of their implicit biases, (2) understand the relationship between implicit biases and the quality of arguments (i.e. unfounded ad hominem arguments), and (3) learn how to engage in meaningful classroom discussions.